Records of vagrant and visitor bird species in the Fildes Region, King George Island, Maritime Antarctic, between 1980 and 2023 - Braun, C.; Grämer, H.; Peter, H.-U. (Ukrainian Antarctic Journal, 2023)
We provide information on vagrant and visitor bird species recorded in the Fildes Region (King George Island, South Shetlands, Antarctic) during the long-term bird monitoring programme between the 1979–1980 and 2022–2023 seasons. The total ice-free territory covers approximately 35 km2, making it one of the largest ice-free areas in the Western Antarctic Peninsula region. In addition to 13 breeding and one potentially breeding bird species, we recorded 28 non-breeding bird species. Of these non-breeding bird species, we defined 18 as vagrants and 10 as visitors. The vagrant and visitor bird species recorded were representatives of the families Spheniscidae, Diomedeidae, Procellariidae, Pelecanoididae, Laridae, Ardeidae, Scolopacidae, and Anatidae. Furthermore, we include information on the frequency of observations of bird species that do not breed in the study area. Most frequently observed were white-rumped sandpiper, cattle egret, emperor penguin, macaroni penguin, and king penguin. These data contribute to knowledge of rare birds in the Antarctic. Together with similar studies, this information may provide valuable clues to unusual environmental conditions that allow vagrants to reach regions beyond their usual distribution range. Furthermore, long-term data on rare bird sightings can indicate a potential expansion of the breeding range of individual species. Such studies may be relevant for the evaluation of environmental changes that are already occurring as a result of current climate change, e.g., changes in sea ice cover or food web structures.